Evolution of the past anterior in the Portuguese language - Hricsina, Jan (Romanica Olomucensia, 2017)
The aim of this article is to analyze the frequency and use of the past anterior ('pretérito anterior') in the evolution of the Portuguese language. The author studies the occurrence of this tense in various types of sentences (syntactic aspect) and various temporal meanings that it expresses (semantic aspect). The analysis is performed via the diachronic linguistic corpus www.corpusdoportugues.org.
Keywords: past anterior; Portuguese; corpora analysis; diachronic linguistics; functional linguistics